Direct calculation of distortion energies in colloidal liquid crystals from single-particle data - Klop, K; Farmer, C; Dullens, R; Aarts, D (Taylor and Francis, 2015)
We report a method to calculate distortion energies of a colloidal liquid crystal from single-particle data via a triangulation of the particle positions followed by a linear interpolation of the particle orientations. Our method provides local information on the strength and type of distortions present in a liquid crystal. We validate our method by applying it to artificially generated data and show that the results are in good agreement with exact calculations of the distortion energy. We further illustrate our method by using it on laser scanning confocal microscopy images of the nematic phase of fd-virus particles in wedge-shaped microfluidics channels.